Lignification-mimetic dehydrogenative diphenoquinone synthesis and electrochemical CO2 capture - Kim, Hyeyun; Shinnawy, Omer; Ulusoy, Seda; Salazar-Alvarez, German; Tran, Ngoc Tuan; Cho, Hyesung; Sung, Changmin; Kim, Seung-Soo; Koo, Bonwook; Jeong, Keunhong; Amini, Kiana; Kim, Kwang Ho (Royal Society of Chemistry, 2026)
Sustainable mitigation of atmospheric CO2 requires not only efficient capture technologies but also environmentally responsible production of the materials that enable them. Many capture systems rely on materials synthesized via energy-intensive, multi-step processes from non-renewable feedstocks. To create truly sustainable solutions, there is a critical need for green synthetic pathways that minimize the overall carbon footprint of capture technologies from cradle to grave. Here, we report a diphenoquinone-based CO2 capture material synthesized from the lignin-derived monomer via an enzymatic coupling reaction, establishing a sustainable route under mild, aqueous conditions without complex purification. The reaction selectively forms a crystalline C4–C4′ linked diphenoquinone, confirmed by comprehensive spectroscopic analyses, and avoids the structural heterogeneity typical of lignin-derived products. The resulting molecule exhibits a positive redox potential and robust reversibility, enabling electrochemical CO2 capture and release with a specific capacity of 1.9 mmol g−1. While initial performance is limited by the physical stability of the reduced species, this work establishes a new paradigm for lignin valorization by transforming renewable phenolics into discrete, functional molecules for CO2 capture, and offers a broadly applicable platform for green synthesis of bio-derived quinones, providing a foundation for sustainable technologies within a circular carbon economy.